Evolution Law of Overburden Longitudinal Connected Fissures in a Shallowly Buried Coal Face with Thin Bedrock - Housheng Jia; Kun Pan; Luyao Wang; Shaowei Liu; Mengxiong Fu; Xiang Ji (Advances in Civil Engineering)
Longitudinal connected fissures in a shallowly buried coal face with thin bedrock are the main factor causing sand-burst accidents, water-burst accidents, and abnormal increases in water inflow. To understand the evolution of longitudinal connected fissures and propose method for controlling such fissures, 3-1 Coal of the Jinjie Coal Mine in Shendong Coal Group, China, was used as a case study. Physical simulation, numerical simulation, field measurements, and other measures were carried out to analyze thoroughly the opening and closure of fissures. At the same time, the stage characteristics of fissures evolution process are also obtained. The results indicate that when periodic weighting occurs, a longitudinal connected fissure starts to open. As the coal face moves on, the fissure expands gradually with the dynamic changes in horizontal force and rock dislocation; when the expansion reaches its limit, the key rock falls and the longitudinal connected fissure rapidly closes. With the advent of the next periodic weighting, the longitudinal connected fissure compacts further and the next longitudinal connected fissure appears. The formation of longitudinal connected fissures is described with reference to three factors: the advancement speed of the coal face, the holding power of the hydraulic support, and the filling degree of the goaf area, all of which can be easily controlled by engineering means. This study provides a basis for control of sand-burst accidents, water-burst accidents, and abnormal increase in water inflow in a shallow coal face with thin bedrock.